2011
DOI: 10.3892/mmr.2011.420
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of esculetin on migration, invasion and matrix metalloproteinase-9 expression in TNF-α-induced vascular smooth muscle cells

Abstract: Abstract. esculetin, a potent non-competitive inhibitor of lipoxygenase, has been shown to inhibit vascular smooth muscle cell (VSMc) proliferation. However, the effect of esculetin on the matrix metalloproteinase-9 (MMP-9) regulation responsible for cell migration and invasion has not been previously investigated. The results of the present study showed the esculetin (12.5-25 µg/ml) induced the inhibition of migration and invasion in tumor necrosis factor-α (TnF-α)-treated VSMc, as demonstrated by a matrigel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The cell cycle profiles in cells expressing HPV E7 under hypoxia were not clear. Glioma cells expressing HPV-16 E7 showed a concomitant decrease in G1 and S phases subject to hypoxia 34 . Here we demonstrated that HPV-16 E7 abrogates G1 checkpoint under hypoxia and rendered cells enter into S-phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell cycle profiles in cells expressing HPV E7 under hypoxia were not clear. Glioma cells expressing HPV-16 E7 showed a concomitant decrease in G1 and S phases subject to hypoxia 34 . Here we demonstrated that HPV-16 E7 abrogates G1 checkpoint under hypoxia and rendered cells enter into S-phase.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, HPV E7 increases HIF-1α mediated transcription by inhibiting the binding of histone deacetylases 31 , leading to HIF-1α accumulation and VEGF expression, which may contribute to enhanced angiogenesis 32, 33 . Glioma cells expressing HPV-16 E7 showed a G2/M arrest with concomitant decrease in G1 and S phases subject to hypoxia 34 . The cell cycle profiles in other types of cells expressing HPV E7 under hypoxia remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table I, only two 4 . Potentials are given with respect to a cadmium-saturated mercury amalgam reference electrode in contact with DMF saturated with both cadmium chloride and sodium chloride; this electrode has a potential of -0.76 V versus SCE at 25 • C. For the cyclic voltammogram recorded with glassy carbon, the potential was scanned from 0 to -2.0 to 0 V; for the cyclic voltammogram recorded with silver, the potential was scanned from 0 to -1.8 to 0 V. cathodic peaks are observed when silver is employed as an electrode for compounds 2a-5a; we believe that these two peaks correspond to the first two stages for the reduction of 1a.…”
Section: Resultsmentioning
confidence: 96%
“…1 Coumarin and its derivatives exhibit biological activity and could possibly be used as anti-coagulant, 2 antitumor, 3 anti-inflammatory, 4 antibiotic, 5 anti-HIV-1, 5 anti-diabetic, 6 and anti-depressant drugs. 6 Two of the most well-known coumarin derivatives are (RS)-4-hydroxy-3-(3-oxo-1-phenylbutyl)-2H-chromen-2-one (Warfarin) and its sodium salt (Coumadin), both of which are prescribed as anti-coagulants.…”
mentioning
confidence: 99%
“…Commonly used TNFα concentrations with physiological effects are between 10–100 ng/ml [29], [30], [31]. We used concentration of 50 ng/ml for our studies.…”
Section: Discussionmentioning
confidence: 99%